Women in management and the issue of gender-based barriers: An empirical study of the business sector in Europe - Claudia Lamberti (European Institute for Knowledge & Value Management (EIKV), 2018)
This thesis focuses on gender-based barriers in the business world that primarily concern women in leading positions. Being aware that inequalities in business still exist today and are increasingly discussed in public, the objective of this thesis is to find out how women suffer from discrimination and what is done in order to overcome these barriers. The primary focus in this evaluation is on women in management positions as special measures have been exclusively implemented for this type of woman (e.g. women's quota). The influence of stereotypes and clichés is only one of the reasons why women see themselves at a disadvantage compared to men in the labor market. Even today, the very traditional distribution of roles still determines peoples' perception. The vision of a woman as a housewife and mother and the father as the sole breadwinner is still entrenched in our society, even though this constellation is only rarely to be found. Today, more and more women enjoy tertiary education and enter the labor market. With the increase in knowledge, the desire to achieve decision-making positions also naturally grows. However, women are finding their way into management at a much slower rate as one would expect. The question arises why women seem to have to work harder in order to receive the deserved promotion and recognition. Furthermore, hearing about the women's quota and increasing discussions about equal salaries add to the impression of a very diverse business world. How this image corresponds to reality is one of the goals of this thesis.
Keywords: 650